Environment and tourism - Holden, Andrew, 1960- (Routledge, Taylor & Francis Group, 2016)
The global demand for tourism continues to increase as economic growth creates opportunities for its consumption as a lifestyle option across cultures. The spatial reach of recreational tourism into remoter environments reflects a desire to reconnect to nature that is partially created by the global trend toward urbanisation.